Newsgame como produto da narrativa jornalística transmidiática - Souza, Haryson Alves de (2018)
From the study of the production of newsgames, online interactive games derived from news or real events, such as practices of multiplatform journalism, we intend to detect similar characteristics between the spheres of information and entertainment, in this case, journalism and games, as a sign of new possibilities in the elaboration of journalistic materials and narratives. From this clipping, three news games were selected; “GetBadNews”, “Playspent” and “#Hacked”, from which trends, technologies and concepts that, aided by aspects of digital journalism, also called webjournalism, will not only supplant the idea that newsgames are examples of a transmissive journalism, as Canavilhas points out (2013), but also to be able to reflect on new narrative paths for the development of these products, which, despite being audiovisual, communicate from the creation of contexts in which the web user can immerse and perform different from that used by other traditional audiovisual media. Therefore, this research intends to indicate that the characteristics used in the entertainment narratives, inserted in the context of the culture of convergence, can also represent different ways of constructing the journalistic narrative, which is interactive and participatory in communication.